A Twelve-Year Experience in Ambulatory Surgery within Urology. (16th February 2012) - Navalón, Pedro; Pallás, Yoni; Navalón, Victor; Ordoño, Felipe; Monllor, Elisa
Abstract : Purpose . The aim of this study is to show you the results we obtained through the integration of the Urology Department into the Ambulatory Surgery Unit for the very first twelve years. Scope . We will explain both the criteria we followed for patients to join in and the surgical and anesthetic procedures we used with those 1544 patients who were ambulatory subjected to urological diseases. After those patients were treated, they reached up to 95% of reasonable results. Conclusions . Most of urological patients liable to have surgical treatment are bound to be included in an ambulatory surgery program, which implies neither a worse healthcare service standard nor a worse satisfaction in patients.